A Cross-Linguistic Study of Individual Differences in Speech Planning - Swets, Benjamin; Fuchs, Susanne; Krivokapić, Jelena; Petrone, Caterina (Frontiers in Psychology, 2021)
Although previous research has shown that there exist individual and cross-linguistic differences in planning strategies during language production, little is known about how such individual differences might vary depending on which language a speaker is planning. The present series of studies examines individual differences in planning strategies exhibited by speakers of American English, French, and German. Participants were asked to describe images on a computer monitor while their eye movements were monitored. In addition, we measured participants’ working memory capacity and speed of processing. The results indicate that in the present study, English and German were planned less incrementally (further in advance) prior to speech onset compared to French, which was planned more incrementally (not as far in advance). Crucially, speed of processing predicted the scope of planning for French speakers, but not for English or German speakers. These results suggest that the different planning strategies that are invoked by syntactic choices available in different languages are associated with the tendency for speakers to rely on different cognitive support systems as they plan sentences.